1987
DOI: 10.1159/000199478
|View full text |Cite
|
Sign up to set email alerts
|

Time Relationships between Cessation of Smoking and Onset of Ulcerative Colitis

Abstract: From 5 centres 154 patients with ulcerative colitis and a history of smoking completed a questionnaire about the temporal relationship between diagnosis of colitis and cessation of smoking. One hundred and thirty-eight of these were ex-smokers and 107 (69.5%) had stopped smoking before the diagnosis of colitis was made. Fifty-six patients (52%) developed colitis within 3 years of stopping smoking. The findings suggest that smoking exerts protective effect against the development of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 5 publications
9
38
0
2
Order By: Relevance
“…Current smoking decreased the risk for UC (OR: 0.58; 95% CI: 0.45-0.75), while former smoking was associated with an increased risk (OR: 1.79; 95% CI: 1.37-2.34). Interestingly, in patients who stopped smoking, UC developed in 52% of patients, in the first three years after cessation, as reported by Motley et al [12] in concordance with other studies [13] . In contrast, active smoking in early childhood was associated with a gradually increased risk for developing UC (OR for smoking start < 10 years: 7.02 and < 15 years: 3.46) [14] .…”
Section: Risk For Developing Ulcerative Colitissupporting
confidence: 87%
See 1 more Smart Citation
“…Current smoking decreased the risk for UC (OR: 0.58; 95% CI: 0.45-0.75), while former smoking was associated with an increased risk (OR: 1.79; 95% CI: 1.37-2.34). Interestingly, in patients who stopped smoking, UC developed in 52% of patients, in the first three years after cessation, as reported by Motley et al [12] in concordance with other studies [13] . In contrast, active smoking in early childhood was associated with a gradually increased risk for developing UC (OR for smoking start < 10 years: 7.02 and < 15 years: 3.46) [14] .…”
Section: Risk For Developing Ulcerative Colitissupporting
confidence: 87%
“…In intermittent smokers, many patients note symptom exacerbation when they stop smoking, followed by symptom relief when they smoke again [12] . In contrast, almost half of the intermittent smokers thought that their colitis symptoms improved while smoking at least 20 cigarettes per day [32] .…”
Section: Effect Of Smoking and Its Cessation On Clinical Course And Ementioning
confidence: 99%
“…Therefore, the nicotine transport system is suggested to be independent of the tertiary amine transport system. There has been overwhelming epidemiological evidence that smoking protects against ulcerative colitis (Motley et al, 1987;Odes et al, 2001). The mechanisms through which nicotine may affect the course of colitis may be relevant to the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ulcerative colitis usually occurs in nonsmokers, and especially among former smokers with ulcerative colitis, the disease typically begins after smoking cessation (Motley et al, 1987;Odes et al, 2001). Although the precise mechanisms of this protective role of tobacco smoke are not clear, nicotine, known to be a major psychoactive compound of tobacco smoke, is suggested to play a major role in it.…”
mentioning
confidence: 99%
“…[73][74][75] In addition, many ulcerative colitis patients noted disease exacerbation upon cessation of smoking, whereas symptoms relief is reported when smoking is resumed. 76 Although there is no clear explanation for this difference, a recent report using two models of murine colitis mimicking Th1 or Th2 type of inflammation has shown that the divergent effect of nicotine may be explained by the upregulation of the α7nAChR by a Th2 inflammatory response (ulcerative colitis) but not by a typical Th1/Th17 inflammatory response. 77 Assuming that the therapeutic response of nicotine (or smoking) is mediated by α7nAChR, these findings may explain the differential effect of smoking in Crohn's versus ulcerative colitis patients.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%